(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
Modern companies need knowledge and information in connection with the development of products and services and the desire to current is balanced between consistent quality. In conclusion, it must be emphasized that due to the prospective orientation of benchmarking is particularly useful as a tool to support strategic management. In contrast to the classical methods of comparison, has a much greater regularity and professionalism in the search for rational methods. This mechanism creates the conditions for the success of the optimization measures undertaken by the ease of coupling with the system of motivation. It should also be emphasized that carried out in connection with the benchmarking studies and analyzes can also inspire a completely new policies, creating opportunities to become a leader in its industry.